2011
DOI: 10.1021/ja2013517
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Fatty Aldehydes to Alka(e)nes and Formate by a Cyanobacterial Aldehyde Decarbonylase: Cryptic Redox by an Unusual Dimetal Oxygenase

Abstract: Cyanobacterial aldehyde decarbonylase (AD) catalyzes conversion of fatty aldehydes (R-CHO) to alka(e)nes (R-H) and formate. Curiously, although this reaction appears to be redox-neutral and formally hydrolytic, AD has a ferritin-like protein architecture and a carboxylate-bridged di-metal cofactor that are both structurally similar to those found in di-iron oxidases and oxygenases. In addition, the in vitro activity of the AD from Nostoc punctiforme (Np) was shown to require a reducing system similar to the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
174
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(191 citation statements)
references
References 42 publications
13
174
3
1
Order By: Relevance
“…These results do not support the function of CER1 as a potentially redox-neutral decarbonylase proposed by early biochemical studies (Cheesbrough and Kolattukudy, 1984;Vioque and Kolattukudy, 1997;Schneider-Belhaddad and Kolattukudy, 2000). However, recent work on cyanobacterial alkane biosynthesis showed that, in vitro, long-chain aldehyde decarbonylation, catalyzed by a di-iron enzyme, strictly requires a reducing system to produce alkanes in both O 2 -dependent and -independent reactions (Das et al, 2011;Li et al, 2011). Based on these latest mechanisms and our data, we propose that CYTB5 act as a cofactor of redox-dependent CER1 activity in the CER1/CER3 VLC alkane-forming complex.…”
Section: Cytb5s As Electron Transfer Components For Vlc Alkane Synthesiscontrasting
confidence: 57%
See 1 more Smart Citation
“…These results do not support the function of CER1 as a potentially redox-neutral decarbonylase proposed by early biochemical studies (Cheesbrough and Kolattukudy, 1984;Vioque and Kolattukudy, 1997;Schneider-Belhaddad and Kolattukudy, 2000). However, recent work on cyanobacterial alkane biosynthesis showed that, in vitro, long-chain aldehyde decarbonylation, catalyzed by a di-iron enzyme, strictly requires a reducing system to produce alkanes in both O 2 -dependent and -independent reactions (Das et al, 2011;Li et al, 2011). Based on these latest mechanisms and our data, we propose that CYTB5 act as a cofactor of redox-dependent CER1 activity in the CER1/CER3 VLC alkane-forming complex.…”
Section: Cytb5s As Electron Transfer Components For Vlc Alkane Synthesiscontrasting
confidence: 57%
“…] functionally related to nonheme di-iron enzymes (Das et al, 2011;Li et al, 2011). In addition, CER1 and CER3 possess the functionally uncharacterized WAX2 domain at their C termini ( Figure 5A; see Supplemental Figure 7 online) that we also partially identified at the C terminus of the cyanobacterial FAAR protein (see Supplemental Figure 7 online).…”
Section: Toward the Understanding Of The Vlc Alkane-forming Catalyticmentioning
confidence: 91%
“…Cyanobacterial ADOs are small proteins of 220-250 amino acids, which catalyze the last step of alka(e)ne biosynthesis. These enzymes, which were initially named aldehyde decarbonylase (ADC), given their function of converting Cn fatty aldehydes to formate and the corresponding Cn-1 alka(e)nes [1,19,22], were finally redesignated as aldehyde-deformylating oxygenases (ADOs) because of the oxygenative nature of the reaction they catalyzed [20,21,23]. Dendograms of ADO did not correspond to a classical cyanobacterial phylogeny when compared with the phylogenetic trees of 16S rDNA or AAR (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cyanobacterial ADOs are readily purified from heterologous expression systems, are active in vitro, and a crystal structure of the enzyme was determined as part of a structural genomics effort (Protein Data Bank 2OC5, Joint Center for Structural Genomics). ADO converts aldehydes to n-1 alkanes with the aldehyde C1 released as formic acid (8,9). Electrons required for the reaction can be provided by NADPH via ferredoxin-NADP reductase (FNR), and ferredoxin (Fd) (7), or via the chemical mediator phenazine methosulfate (PMS) (10).…”
mentioning
confidence: 99%